Design and Force Analysis of a Movable Teeth Driving System Integrated with Shape Memory Alloy - Chai Zongxing; Xu Lizhong; Jiang Yaqi; He Xiaodong (Jixie chuandong)
A movable teeth driving system integrated with shape memory alloy（ SMA） and movable teeth reduction drive is proposed,which used SMA wires to drive the movable teeth transmission system and realize torque output. It has the advantages of small size,low speed and large torque. The structure and working principle of the SMA movable teeth driving system are introduced,the main performance design process and parameters of the system are given. And force conditions of movable teeth transmission system in the system are analyzed,the forces on the movable teeth of wave generator,movable teeth rack and center wheel changed along with output shaft angles are obtained. The results laid a theoretical basis on dynamics analysis and experimental research of the SMA movable teeth driving system.